Confronting the realities of wastewater use in agriculture - International Water Management Institute (International Water Management Institute, 2003)
Based on research presented in ?Urban-Wastewater Reuse for Crop Production in the Water-Short Guanajuato River Basin Mexico (IWMI) Research Report 41) by C. Scott, J.A. Zarazua and G. Levine; ?Urban Wastewater: AValuable Resource for Agriculture: A Case Study from Haroonabad, Pakistan (IWMI Research Report 63)? by W. van der Hoek, M. Ul Hassan, J. Ensink, S. Feenstra, L. Rachid-Sally, S. Munir, R. Aslam, N. Ali, R. Hussain and Y. Matsuno: and ?Use of Untreated Wastewater in Peri-Urban Agriculture in Pakistan: Risks and Opportunities (IWMI Research Report 64)? by K Ensink, W. van der Hoek, Y. Matsuno, S. Munir and R. Aslam.